Formation of Digital Competence of Teachers in General ‎Secondary Education in The Context of The Educational Hub’s ‎Activities - Biloisova, Nadiia; Hordiienko , Tetiana; Filonenko , Olena; Bobro , Artur; Arnauta , Nataliia; Dolmatova , Maryna (International Journal of Basic and Applied Sciences, 2025)
The purpose of the article is to examine the methodological features of forming digital competence among general secondary education ‎teachers through the activities of educational hubs and to reveal the potential for using digital services in teacher training. This study ‎addresses one of the most important issues in the modern educational process – the formation of digital competence among educators, which ‎is viewed as a key condition for the New Ukrainian School concept and an essential skill for life in contemporary society. An analysis of ‎scientific approaches to the interpretation of "digital competence" term is conductedю Researchers consider a teacher’s digital competence ‎not only as a set of knowledge, skills, and abilities necessary for the effective use of information and communication technologies (ICT) in ‎the educational process; it also encompasses the ability to integrate digital tools into the educational process, create interactive content, ‎organize distance learning, and ensure safety in the digital environment. The results of a study of digital competence level among future ‎general secondary education (GSE) teachers are described. The study was conducted at Nizhyn State University named after Mykola Hohol. ‎The sample consisted of 110 students from the 1st to 4th years in the field of Education/Pedagogy. The study results confirmed the ‎necessity and interest of students in enhancing their digital competence, leading to the establishment of an educational hub for future teachers. ‎Scientific approaches are summarized, and a unique definition of the term "educational hub" is formulated, which is viewed as a center that ‎unites various educational initiatives with a focus on innovation and modern teaching approaches. The main idea of such a hub is to create ‎an environment where students, educators, and teachers can collaborate, share knowledge, and generate new ideas. The contributions of ‎faculty within the Department of Pedagogy, Primary Education, Psychology, and Management, along with higher education students, in the ‎activities of various educational hubs are described, highlighting lesson developments and author projects using different electronic ‎educational resources. The results of a training program within the educational hub focused on forming digital competencies for future ‎teachers are outlined, demonstrating its effectiveness. The program content included acquiring new knowledge and skills, mastering various ‎digital technologies, the ability to search for, analyze, and critically evaluate information from diverse sources, and skills in creating games, ‎presentations, interactive exercises, and mind maps. It also includes creating engaging content; developing critical thinking abilities and ‎problem-solving skills through digital technologies, and selecting appropriate digital tools to achieve educational goals, as well as ‎developing interactive tasks and projects‎.